Combined Effects in Singular Elliptic Problems in Punctured Domain. (30th January 2021) - Bachar, Imed; Mâagli, Habib; Eltayeb, Hassan
Abstract : The paper deals with nonlinear elliptic differential equations subject to some boundary value conditions in a regular bounded punctured domain. By means of properties of slowly regularly varying functions at zero and the Schauder fixed-point theorem, we establish the existence of a positive continuous solution for the suggested problem. Global estimates on such solution, which could blow up at the origin, are also obtained.